Characterization of smallholder pig production systems in mountainous area of North Vietnam - Lemke, U.; Thuy, L.T.; Zarate, A.V.; Kaufmann, B.; Vang, N.D. (2002)
Situation of farmers in Vietnam’s mountainous area is hampered by low and unsteady resource availability and less developed infrastructure. Smallholders seek to improve their livelihood by extending livestock husbandry with main focus on pig keeping. Local pig breeds are progressively replaced by genotypes with higher production potential. Keeping high yielding genotypes may generate higher revenues from pig production but also implies an economic risk for farmers due to higher input required. This study assesses the suitability of local pig breeds and introduced improved genotypes for smallholders in different production systems. Pig production intensity, farmers’ production aims and management strategies are described. Reproductive and production performances of genotypes are given. Out put from pig production is determined. Data collection was carried out in two research periods in 2001 and 2002 in North Vietnam, Son La province. Four selected villages of ethnic Black Thai cover a gradient from semi-intensive pig production in the mountain valley, near town to extensive pig production at the hillside, far from town. Research methods include structured household interviews, communication tools (from RRA methodology), recording production/ reproduction data and weighing pigs. Preliminary results show that near town farmers keep the introduced Mong Cai pig with relatively high performance. The more market-oriented pig production returns higher cash revenue, but requires higher production costs. Far from town, pig production fulfils mainly social functions. Farmers keep the local Ban pig with low performance and yield lower cash revenue, however, have lower production costs. Data analysis yielded factors influencing variation of productive/ reproductive performances on-farm and production inefficiency. The results are prerequisites fro the set up of on-farm performance testing and thereby for the determination of production efficiency of different pig genotypes in the production systems investigated.